"(xy^2-x^2)dx+(3x^2y^2+x^2y-2x^3+y^2)dy=0\\\\\nP(x,y)=xy^2-x^2\\\\\nQ(x,y)=3x^2y^2+x^2y-2x^3+y^2\\\\\n\\frac{\\partial P}{\\partial y}=2xy\\\\\n\\frac{\\partial Q}{\\partial x}=6xy^2+2xy-6x^2\\\\\n\\frac{\\partial P}{\\partial y}\\neq\\frac{\\partial Q}{\\partial x}\\\\\n\\Psi(y)=\\frac{\\frac{\\partial P}{\\partial y}-\\frac{\\partial Q}{\\partial x}}{-P}=\\\\\n=\\frac{2xy-(6xy^2+2xy-6x^2)}{-(xy^2-x^2)}=\\frac{-6xy^2+6x^2}{x^2-xy^2}=\\frac{6(xy^2-x^2)}{xy^2-x^2}=6\\\\\n\\mu(y)=e^{\\int\\Psi(y)dy}=e^{\\int6dy}=e^{6y}"
we multiply the equation by "e^{6y}"
"(xy^2-x^2)e^{6y}dx+\\\\\n+(3x^2y^2+x^2y-2x^3+y^2)e^{6y}dy=0\\\\\nP_1(x,y)=(xy^2-x^2)e^{6y}\\\\\nQ_1(x,y)=(3x^2y^2+x^2y-2x^3+y^2)e^{6y}\\\\\n\\frac{\\partial P_1}{\\partial y}=6e^{6y}(xy^2-x^2)+e^{6y}(2xy)=\\\\\n=e^{6y}(6xy^2+2xy-6x^2)\\\\\n\\frac{\\partial Q_1}{\\partial x}=e^{6y}(6xy^2+2xy-6x^2)\\\\\n\\frac{\\partial P_1}{\\partial y}=\\frac{\\partial Q_1}{\\partial x}"
Then there is a function "u(x,y)" such that
"\\frac{\\partial u}{\\partial x}=(xy^2-x^2)e^{6y}\\\\\n\\frac{\\partial u}{\\partial y}=(3x^2y^2+x^2y-2x^3+y^2)e^{6y}\\\\\nu(x,y)=\\int(xy^2-x^2)e^{6y}dx=\\\\\n=(\\frac{x^2}{2}y^2-\\frac{x^3}{3})e^{6y}+\\phi(y)\\\\\n\\frac{\\partial{u(x,y)}}{\\partial{y}}=6e^{6y}(\\frac{x^2y^2}{2}-\\frac{x^3}{3})+yx^2e^{6y}+\\phi'(y)=\\\\\n=e^{6y}(3x^2y^2-2x^3+yx^2)+\\phi'(y)\\\\\ne^{6y}(3x^2y^2-2x^3+yx^2)+\\phi'(y)=\\\\\n=e^{6y}(3x^2y^2+x^2y-2x^3+y^2)\\\\\n\\phi'(y)=y^2e^{6y}\\\\\n\\phi(y)=y^2\\frac{e^{6y}}{6}-y\\frac{e^{6y}}{18}+\\frac{e^{6y}}{108}"
solutions of the equation
"(\\frac{x^2}{2}y^2-\\frac{x^3}{3})e^{6y}+y^2\\frac{e^{6y}}{6}-y\\frac{e^{6y}}{18}+\\frac{e^{6y}}{108}=C"
Comments
Leave a comment